Dynamic Change in Insulin Resistance Induced by Free Fatty Acids Is Unchanged Though Insulin Sensitivity Improves Following Endurance Exercise in PCOS - Aye, Myint Myint; Butler, Alexandra E.; Kilpatrick, Eric S.; Kirk, Richard; Vince, Rebecca; Rigby, Alan S.; Sandeman, Derek; Atkin, Stephen L. (Frontiers in Endocrinology, 2018)
Background: Insulin resistance (IR) is the hallmark of PCOS and it is known that exercise may decrease it. What is unknown is whether exercise may mechanistically alter the underlying IR, attenuating the dynamic lipid induced IR in insulin resistant subjects. Methods: Twelve women with polycystic ovary syndrome (PCOS) and ten age and body mass index matched controls completed an eight week supervised exercise program at 60% maximal oxygen consumption. Before and after the exercise program, all participants underwent hyperinsulinaemic euglycaemic clamps with either saline or intralipid infusions. Skewed data were log transformed and expressed as mean ±SEM. Results: Before exercise, women with PCOS had a higher HOMA-IR and lower VO2 max than controls. Compared to saline, lipid infusion lowered the rate of insulin stimulated glucose disposal (M value; mg/kg/min) by 67±5% (from 0.5±0.03 to -0.25±0.2, p=0.01) in PCOS, and by 49±7% (from 0.65±0.06 to 0.3±0.1, p=0.01) in controls. The M value was significantly less in PCOS compared to controls for both saline (p<0.01) and lipid (p<0.05) Endurance exercise in PCOS improved VO2 max and HOMA-IR, but not weight, to those of pre-exercise control subjects. The glucose disposal rate during the lipid infusion was reduced following exercise in PCOS, indicating decreased IR (67±5% vs. 50±7%, p=0.02), but IR was not altered in controls (49±7% vs. 45±6%, p=0.58). The incrementally increased IR induced by the lipid infusion did not differ between controls and PCOS. Conclusion: Insulin sensitivity improved with exercise in the PCOS group alone showing that IR can be modified, though likely transiently. However, the maximal IR response to the lipid infusion did not differ within and between control and PCOS subjects, indicating that the fundamental mechanism underlying insulin resistance was unchanged with exercise.